The “Self” as Sufferer - Perkins, Judith (1992)
The early Roman Empire provides little evidence for the personal religious feelings of its inhabitants; only a few texts reflect what we would call individual testimony of personal religious experience. The works of second-century authors which in fact display such religious feelings often offend modern sensibilities. Commentators have described Aelius Aristides' Orationes sacrae, the letters of Ignatius of Antioch, and the Meditations of Marcus Aurelius as neurotic or pathological. In a recent book, for example, Charles A. Behr introduced a discussion of Aristides with the deprecatory comment: “peculiar and unpleasant though his personality may seem to us today.” The same offense, moreover, is ascribed to all three men, namely, an inordinate fixation on bodily pain and suffering. Interpreting these authors' textual emphasis on pain as merely a reflection of the pathology of aberrant individuals of the early empire is an unfair simplification of the texts. Such a reading prevents the recognition that their emphasis on pain and suffering reflects a widespread cultural concern of the period that used representations of bodily pain and suffering to construct a new subjectivity of the human person.